An adaptive object design for CAD engineering databases - Nguyen Vinh Quang; Zhao, Ming; Huynh, Ngoc Phien; Bohez, Erik L.J.; Ecumenical Scholarships Programme(ESP), Bfdw (Bangkok : Asian Institute of Technology, 1991)
The purpose of this thesis is the design of adaptive 3D object for intelligent CAD. The meaning of adaptivity can be understood as the characteristic of self- changing to adapt itself to the user's requirements. The model is broken down into primitive objects. Each object contains its own boundary data structure and geometric constraints that permit the object to adapt itself to global changes of the complex model. The last result of the model depends on the satisfactions of all objects' geometric constraints. The system was implemented by applying the object-oriented programming, a newly-developed technique in the recent years. An interactive system with a restricted set of commands was designed to display an adaptive model on the screen. Through command entering, the user can perform simple geometric modelling on it.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1991
Keywords: Computer-aided design